Justification of Open Pit Mining Technology for Flat Coal Strata Processing in Relation to the Stratigraphic Positioning Rate - Tyulenev M. A. Maksim Anatolievich; Gvozdkova T. N. Tatjyana Nikolaevna; Zhironkin S. A. Sergey Aleksandrovich; Garina E. A. Ekaterina Aleksandrovna (2017, 2017)
Title screen